Prevalence of homosexuality among boarding secondary school students in Lilongwe rural. - Hara, Modestar (Kamuzu University of Health Sciences, 2022)
The aim of the study was to find out the prevalence of homosexuality among boarding secondary school students in Lilongwe rural. Specifically the study assessed student's knowledge on homosexuality and HIV, contributing factors to the practice of homosexuality, the kinds of sexual practices that they indulge in and the use of protective measures against HIV and STIs. A quantitative study design was used to collect data from 81 students studying in single sex (a boys only and a girls only) boarding secondary school. The health belief model developed in 1950's by social psychologists was used to guide this study. Data was collected using questionnaires and analysed using statistical package for social sciences (SPSS) version 12. The analysed data has been presented in tables, graphs and pie charts. The findings of this study have shown that the students had knowledge on homosexuality and HIV transmission. Despite this knowledge the results have shown that the practice of same sexual practices does occur in single sex boarding schools. The reasons for the students engaging in same sex sexual practices included loneliness and pressure from friends. The kinds of sexual practices that they indulge in included digital finger penetration and kissing (among females) and anal sex (among males). The students said there are no protective measures used during these practices because students are confident that the other partner is free of HVI/STIs and that there is no perceived risk for contracting HIV and STIs. The findings of this research study will help to form the basis for a step further in the prevention of HIV and AIDS in young people who indulge in same sex sexual behavior. The results will assist nurses in providing health education concerning HIV transmission and prevention especially to boarding secondary school students. The results will also help students to prevent engaging in risky sexual behaviors like homosexuality and also head teachers and management in boarding secondary schools to guard against this practice among students to prevent the spread of HIV and STIs. The study results will also assist religious leaders in preaching about what the bible says on homosexuality especially to the adolescents and students in boarding schools.